Assessment of patient falls using the world health organization’s international classification for patient safety: a five-year retrospective study - Gulcan Ciftcioglu Yalcin (Journal of the Pakistan Medical Association, 2026)
Aim: To evaluate patient fall incidents using a standardised patient safety classification. Methods: The retrospective, descriptive study was conducted from June to November 2023 in the Mardin province of Turkiye, and comprised data from 10 hospitals related to fall incidents occurring between June 2018 and March 2023. The cases were evaluated in the light of the World Health Organisation's International Patient Safety Classification. Data was analysed using IBM SPSS Statistics software (Version 25.0). Results: Of 140 patients with mean age 50.8. 71 of the patients who experienced a fall were aged